2023
DOI: 10.3390/agriculture13071294
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils as a Dietary Additive for Laying Hens: Performance, Egg Quality, Antioxidant Status, and Intestinal Morphology: A Meta-Analysis

Abstract: This meta-analysis aimed to evaluate the effects of dietary supplementation with essential oils (EOs) on egg production and quality, antioxidant status in blood serum, and the intestinal morphology of laying hens. The data used were obtained from 38 peer-reviewed publications. The effect size was evaluated by weighted mean differences (WMD) between the experimental treatments (diets added with EOs) and the control treatments (diets without EOs). EO supplementation increased (p < 0.001) egg production (WMD =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…Research results have shown that the inclusion of essential nutrients in laying hen diets can be a strategy to improve the quality of eggs [38], and the factors that can influence the extent to which the respective nutrients will be found in the egg require research.…”
Section: Discussionmentioning
confidence: 99%
“…Research results have shown that the inclusion of essential nutrients in laying hen diets can be a strategy to improve the quality of eggs [38], and the factors that can influence the extent to which the respective nutrients will be found in the egg require research.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to improving poultry productivity, there is high interest in enhancing the nutritional and sensory qualities of poultry products (eggs and meat), thereby influencing consumers' preferences and choices, as shown in some of the papers published in this Special Issue. The meta-analysis conducted by Orzuna-Orzuna et al [12] led to the conclusion that supplementing the diet of laying hens with essential oils improves the productive performance (increases egg yield and egg mass and decreases the feed conversion ratio) and egg quality (mineral shell thickness and strength and intensity of the yolk color). In addition, dietary inclusion of essential oils improved blood serum antioxidant status and intestinal morphology in laying hens.…”
mentioning
confidence: 99%